The linkage of EI Nino and La Nina on the environment and resources at Ban Don Bay and Surat Thani : final research report - Absornsuda Siripong (Chulalongkorn University, 2010)
The Landsat data in 3 periods: which are during the El Nino years (1993, 1994,1997 and 2002); the La Nina years (1988, 1998 and 2000); and Normal year (1989, 1996 and 1999), are classified for landuse types and by NDVI (Normalised Difference Vegatation Index), We found that during El Nino years, the rainfall anomalies are minus (less than normal), the air temperature anomalies are plus (hotter than normal), Tapi river dischange anomalies are minus, and NDVI’s are lower than normal (less growing vegetations). During La Nina years, the rainfall anomalies are plus (higher than normal), the air temperature anomalies are minus (colder than normal), the Tapi river dischange anomalies are plus, and NDVI’s are higher than normal (much growing vegetations). In 1998, first half of the year was El Nino, and last half of the year was La Nina. However, we used the data on 27 April 1998, which is in the El Nino period, so it received the impact of El Nino. For fisheries statistics at Surat Thani during El Nino years, the quantity of fish catch and the yields of aquacultures (shrimp and fish) were higher than average. During the La Nina years the same parameters were lower than average the areas of shrimp ponds have been increased with the increasing population. The population of Surat Thani has been increased every year. During the El Nino years, the areas of natural and mangroves were decreased, while during the El Nina years, the areas were increased. El Nino caused higher frequency of tropical cyclone. La Nina also caused tropical cyclone but lesser than El Nino linkage. The linkage of ENSO on MSL is not very clear owing to the small quantity of data. During La Nina years, MSLs show plus and minus anomalies for one each year. However, we may conclude that El Nino causes higher MLS than mean value. El Nino caused lower river runoff than normal. La Nina caused higher runoff than normal.